New bread law boosts cassava sales - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The Federal Government of Nigeria has introduced a law making it compulsory for bakers to use composite flour of 10% cassava and 90% wheat for bread production. The new regulations, which came into force in January 2005, stipulate that the large flour mil